2016
DOI: 10.1016/j.btre.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of succinic acid using crude and purified glycerol from a Crotalaria juncea based biorefinery

Abstract: HighlightsCrotalaria juncea oil is trans-esterified, waste glycerol is separated and purified.Crude, purified and commercial glycerol becomes the major carbon source for E.coli.Succinic acid is produced by batch fermentation of glycerol using Escherichia coli.Aiba-Edward model ranked 1 out of 7 in case of two samples.Process parameters for the batch fermentation are optimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…As shown in Table 1, we found that crude glycerol inhibited glycerol consumption and succinate production. The previous study has also shown that crude glycerol inhibits the production of succinate by E. coli (Sadhukhan et al 2016). In this study, when the simply purified crude glycerol was used as carbon source, the inhibition of glycerol consumption and succinate production was significantly reduced compared with those using crude glycerol.…”
Section: Two-stage Fermentation For Succinate Production Using Differmentioning
confidence: 62%
See 1 more Smart Citation
“…As shown in Table 1, we found that crude glycerol inhibited glycerol consumption and succinate production. The previous study has also shown that crude glycerol inhibits the production of succinate by E. coli (Sadhukhan et al 2016). In this study, when the simply purified crude glycerol was used as carbon source, the inhibition of glycerol consumption and succinate production was significantly reduced compared with those using crude glycerol.…”
Section: Two-stage Fermentation For Succinate Production Using Differmentioning
confidence: 62%
“…To produce succinate from glycerol, different strategies of fermentation based on different engineered strains were applied, such as anaerobic (Zhang et al 2010), micro-aerobic (Blankschien et al 2010) and aerobic (Li et al 2013) cultures. Sadhukhan et al (2016) treated the crude glycerol through several physical-chemical steps: acidification, neutralization, solvent extraction, adsorption, and, finally, pressure filtration through a membrane. Then, the treated glycerol was used as carbon source to produce succinic acid by E. coli (ATCC 8739), but only 1.4 g/L succinic acid was accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of succinic acid in the unknown solutions are estimated using standard curves prepared by plotting peak areas versus known concentrations of succinic acid samples. The entire process is optimized for a maximum production of succinic acid [26].…”
Section: Preparation Of Bio-refined Succinic Acid For Hydrogenationmentioning
confidence: 99%
“…First oil is extracted from the Crotalaria juncea seeds [23], which then gets trans-esterified using traditional and natural catalysts to produce a bio-diesel along with a huge quantity of waste glycerol [24]. The waste glycerol is then purified using sequential desalination [25] and further utilized as the primary substrate for producing bio succinic acid using E.Coli during microbial fermentation [26]. In this particular work, a number of Ru-Co bimetallic catalysts are synthesized with varying contents of Ru.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-PD (Loh and Stasha, 2016;Jun et al, 2010), citric acid (Morgunov et al, 2013), succinic acid (Sadhukhan et al, 2016), ethanol (Chanthoom et al, 2016) and butanol (Jensen et al, 2012). Previously, several bacteria species had been identified for their ability to produce 1,3-PD such as Klebsiella (Wojtusik et al, 2015), Clostridium (Szymanowska-Powalowska, 2014), Enterobacter (Waghmare and Naik, 2016) and Citrobacter (Ferreira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%